Detection of zoonotic bacterial pathogens in multiple hosts using a microbiome approach and molecular characterization of Anaplasma phagocytophilum - Oosthuizen, Marinda C. (University of Pretoria, 2019)
Thesis (PhD)--University of Pretoria, 2019.